Safety and efficacy of stereotactic body radiation therapy combined with S-1 simultaneously followed by sequential S-1 as an initial treatment for locally advanced pancreatic cancer (SILAPANC) trial: study design and rationale of a phase II clinical trial. Issue 12 (1st December 2016) - Zhu, Xiaofei; Ju, Xiaoping; Cao, Fei; Fang, Fang; Qing, Shuiwang; Shen, Yuxin; Jia, Zhen; Cao, Yangsen; Zhang, Huojun
Abstract : Introduction: Upfront surgeries are not beneficial to most patients with pancreatic cancer. Therefore, more emphasis has been placed chemoradiotherapy in locally advanced pancreatic cancer recently. Gemcitabine-based regimens or FOLFIRINOX (a chemotherapy regimen including leucovorin, 5-FU, irinotecan, oxaliplatin) has been proven as a standard chemotherapy in pancreatic cancer. However, severe toxicities may prevent the completion of chemotherapy. S-1 has showed better objective response rates, similar overall survival rates and progression-free survival rates compared with gemcitabine, revealing that S-1 may be a potential candidate in treating pancreatic cancer, especially for patients refractory to gemcitabine. Additionally, stereotactic body radiation therapy with Cyberknife could provide better efficacy than conventional radiotherapy in pancreatic cancer. Therefore, Cyberknife with S-1 simultaneously followed by sequential S-1 as an initial treatment may bring about favourable outcomes but needs further studies. Methods and analysis: The S-1 as an initial treatment for locally advanced pancreatic cancer (SILAPANC) trial is a prospective, single-centre, one armed ongoing study. 190 eligible patients are required to initially receive Cyberknife with 1 cycle of S-1 simultaneously. After the concurrent chemoradiotherapy, 2 or 3 cycles of S-1 are sequentially given. Doses and fractions depend on the locations and volumes of tumours and the adjacent organs at risk. S-1 is taken orally, 2 times a day, at a dose of 80 mg/m 2 for 28 days, followed by a 14-day interval. The primary objectives are overall survival and 1-year, 2-year, 3-year, 4-year and 5-year overall survival rates. The secondary objectives are cancer-specific survival, progression-free survival, time to progression, local control rates, clinical benefit rates, radiation-induced acute and late toxicities, adverse effects of chemotherapy and quality of life of patients. Besides, variables most predictive of prognosis would be identified via multivariate methods. Ethics and dissemination: Approvals have been granted by the Changhai Hospital Ethics Committee (CHEC-2016-032-01). The results will be disseminated in peer-reviewed journals and at conferences. Trial registration number: NCT02704143 ; Pre-results.